A Comparison Between Bonobos and Chimpanzees: A Review and Update. Issue 5 (September 2016) - Gruber, Thibaud; Clay, Zanna
Abstract : Chimpanzees ( Pan troglodytes ) and bonobos ( P. paniscus ) are our closest living relatives, with the human lineage diverging from the Pan lineage only around five to seven Mya, but possibly as early as eight Mya. 1–2 Chimpanzees and bonobos even share genetic similarities with humans that they do not share with each other. 2 Given their close genetic relationship to humans, both Pan species represent crucial living models for reconstructing our last common ancestor (LCA) and identifying uniquely human features. Comparing the similarities and differences of the two Pan is thus essential for constructing balanced models of human evolution. 3